Pendampingan Program Konservasi Lingkungan melalui Tabung Biopori, Pupuk Organik, dan Daur Ulang Plastik di Desa Rangdumulya - Firda Ainun Nisah; Muhammad Ragil Ramadhan; Yoga Ulya Mubarok (Institut Pertanian Bogor, 2025)
The community of Rangdumulya Village faces challenges in processing agricultural and household waste. Sustainable waste management can overcome these issues using biopore tubes, organic fertilizers, and plastic recycling. The purpose of this community service activity is to achieve zero waste in Rangdumulya Village in the form of a clean, healthy environment and a community that is independent in managing waste. The method used consisted of three stages: preparation, socialization, and training. The biopore tube activity on January 11, 2024, with 46 participants, increased knowledge by 39.13%, and eight out of nine groups successfully created biopores tubes. The activity of making liquid organic fertilizer on January 16, 2024, with 34 participants, increased knowledge by 33.33%, and four out of five groups successfully created liquid organic fertilizer. Plastic recycling activity on January 20, 2024, with 73 participants, increased knowledge by 34.22%, and 16 out of 18 groups successfully processed plastic recycling. This indicates that the people of Rangdumulya Village understood the activities that were taught. The Rangdumulya community has successfully carried out this environmental conservation activity independently through two monitoring sessions over two months post-activity.